PENGARUH MOTIVASI, KEMAMPUAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN PETISAH - Hery Irwansyah Sinaga (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of motivation on employees performance. How influence of work ability on employees performance. How influence of work facility on employees performance. How influence of motivation, work ability and work facility on employees performance. The purpose of this research is for know influence and analize of motivation on employees performance. For know influence and analize of work ability on employees performance. For know influence and analize work facility on employees performance. For know influence and analize motivation, work ability and work facility on employees performance. The sample in this research is 88 employees, with data analysis technique used is multiple linear regression analyze. The results of this research explain that motivation effect has a positive and significant on employee performance. Work ability effect has a positive and significant on employee performance. work facility effect has a positive and significant on employee performance. Motivation, work ability and work facility effect have a positive and significant on employee performance